EXPLORING NATIONALISM VALUES IN SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Sri Suryatiningsih, - (2020)
This research investigates the representation of nationalism values in Pathway to English and Bahasa Inggris, the transfer and negotiation of those values through nation and national narratives in English class, and the reflection of nationalism values in students' English vlogs. Descriptive qualitative method was employed in two schools using document analysis, classroom observation, and semi-structured interviews. The nationalism values promoted in textbooks are citizens, cultures, routine deixis, and so on. The nation and national narratives aid the development of students' English skills, nationalism awareness, autonomous learning and engagement. The vlogs reflected the students' localized nationalism using routine deixis, architecture, etc.